2017
DOI: 10.12788/jhm.2721
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Sepsis: Are Two Opinions Better Than One?

Abstract: The diagnosis of sepsis requires that objective criteria be met with a corresponding subjective suspicion of infection. We conducted a study to characterize the agreement between different providers’ suspicion of infection and the correlation with patient outcomes using prospective data from a general medicine ward. Registered nurse (RN) suspicion of infection was collected every 12 hours and compared with medical doctor or advanced practice professional (MD/APP) suspicion, defined as an existing order for ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…However, one study showed that predictions considering ineffective treatment were more valuable when based on collaborative decision-making [ 21 ]. Another study focusing on detecting sepsis showed that the chance of severe sepsis was highest when estimated by two healthcare providers [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, one study showed that predictions considering ineffective treatment were more valuable when based on collaborative decision-making [ 21 ]. Another study focusing on detecting sepsis showed that the chance of severe sepsis was highest when estimated by two healthcare providers [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a singlecenter prospective study by our group, we found that bedside nurses and ordering providers agreed on the presence of infection only 17% of the time (k ¼ 0.12). 52 Furthermore, progression to severe sepsis or shock was significantly higher when both providers suspected infection in a SIRS-positive patient (17.7%) and lowest when neither suspected infection (1.5%), with singleprovider suspicion conferring intermediate risk (6.0%). Studies using EHR data to define infection are equally challenging, as the accuracy of culture orders, antibiotic prescriptions, and other interventions for defining infection are unknown.…”
Section: Non-sirs-based Screening Toolsmentioning
confidence: 93%
“…19 Collaborative care has been shown to improve diagnosis and treatment of various health conditions. [20][21][22][23] A recent workshop recommended that critical care physicians have antimicrobial stewardship as a core competency. 24 However, the recommendation of this group was to incorporate antimicrobial stewardship objectives into critical care training, a daunting task in an already grueling fellowship.…”
Section: Discussionmentioning
confidence: 99%